Study on the Influence of the Wet Clutch Applied Load Way on Its Thermal Structural Stress Field - Chen Yao; Zhang Zhigang; Shi Xiaohui; Liang Meilin; Yin Sheng (Jixie chuandong)
Based on the actual structure and work conditions of wet multi-disc clutch,a finite element analysis model of wet clutch is established by using Abaqus. The Mises stress field of friction pairs in wet clutch is analyzed by the direct thermal structure coupling method,and the influence of the applied load way of piston in wet clutch on the Mises stress field of friction pairs is studied. The results show that the applied load way has an important effect on the maximum stress distribution and axial stress transfer velocity of separator plate. And the bandwidth of high stress area and the velocity of stress transfer along axial direction under uniform load are larger than those in partial load. In addition,the maximum stress and radial stress gradient of separator plate under the partial load way is greater than that under uniform load way.